IMPLEMENTATION OF ONLINE REGISTRATION E-COURT AT INDONESIA RELIGIOUS COURTS - Muhammad, Mukmin; Rahmadina (Universitas Brawijaya, 2023)
The purpose of this study is to know the pattern of service at the Barru Religious Court Office during the Covid-19 pandemic and the implementation of online case registration E-Court of physical distancing at the Religious Court Office during the pandemic. This qualitative research include observation, interviews, documentation. Data analysis involve data reduction, data presentation, and conclusion drafting. The result shows the implementation used in the registration of the first case is online case registration, the second is to get a down-payment interpretation online, the third can make online payments, the fourth can conduct trials online (litigation), the fifth can view calls online, and the sixth can make decisions online. The case registration E-Court has been carried out following PERMA No.1 of 2019 about the electronic case of registration. In particular, at a time when Indonesians are growing more concerned about the Covid-19 virus outbreak, this PERMA is extremely appropriate to be carried out.